PENGEMBANGAN KREATIVITAS PENDIDIKAN ISLAM DI INDONESIA (TELAAH URGENSI PROSES) - Mahmudah Mahmudah (Jurnal Kependidikan, 2014)
Nowadays, the change and the development of society run faster and more dispersely than before. In this era of globalization, Islamic education, as a means to bring out a competent human capital that can compete in the era of 21st century, needs to pay closer attention to the "process" than to the "outcome", and this way can be regarded as an alternative to the development of creativity. This paper shows some significant ideas to explore how to emphazise the "process". The ideas include motivation, learning strategies, self consciousness, work ethic, participatory approach to fostering creativity, musing space, and change in attitudes. With the spirit of change and the passion of work, this paper offers some ideas to foster a good quality of Muslim generation as a solution to the educational crisis of this nation.